Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) Ta có :
\(\frac{3}{4}< \frac{x}{8}< 1\Rightarrow\frac{6}{8}< \frac{x}{8}< \frac{8}{8}\)
=> 6 < x < 8 => x = 7
b) Ta có :
\(\frac{5}{4}< x< \frac{27}{11}\Rightarrow1\frac{1}{4}< x< 2\frac{5}{11}\)
=> x = 2
c) Ta có :
\(1< \frac{4}{x}< 2\Rightarrow\frac{4}{4}< \frac{4}{x}< \frac{4}{2}\)
=> 4 > x > 2 => x = 3
a) \(\frac{3}{4}< \frac{x}{8}< 1\)
=> \(\frac{6}{8}< \frac{x}{8}< \frac{8}{8}\)
=> Vậy \(\frac{x}{8}=\frac{7}{8}\)
b) \(\frac{5}{4}\)\(< \)\(x< \)\(\frac{27}{11}\)
Vì : \(\frac{5}{4}< \frac{8}{4}hay\frac{5}{4}< 2\)
\(\frac{22}{11}< \frac{27}{11}hay2< \frac{27}{11}\)
=> Vậy x = 2
a) ta có: \(\frac{3}{4}< \frac{x}{8}< 1\)
\(\Rightarrow\frac{6}{8}< \frac{x}{8}< \frac{8}{8}\)
=> x = 7
b) ta có: \(\frac{5}{4}< x< \frac{27}{11}\)
\(\Rightarrow1,25< x< 2,45\)
=> x = 2
c)ta có: \(1< \frac{4}{x}< 2\)
\(\frac{4}{4}< \frac{4}{x}< \frac{4}{2}\)
=> 4 > x > 2
=> x = 3
Bài giải
\(\frac{2}{3}+\frac{3}{4}+\frac{4}{5}=\frac{40}{60}+\frac{45}{60}+\frac{48}{60}=\frac{133}{60}\)
\(\frac{8}{5}+\frac{7}{6}+\frac{10}{9}+\frac{1}{2}=\frac{144}{90}+\frac{105}{90}+\frac{100}{90}+\frac{45}{90}=\frac{394}{90}\)
\(\frac{15}{17}-\frac{11}{13}+\frac{3}{26}=\frac{390}{442}+\frac{374}{442}+\frac{51}{442}=\frac{815}{442}\)
\(\frac{9}{12}\text{ x }\frac{4}{3}\text{ : }\frac{8}{5}=\frac{9}{12}\text{ x }\frac{4}{3}\text{ x }\frac{5}{8}=\frac{9\text{ x }4\text{ x }5}{12\text{ x }3\text{ x }8}=\frac{5}{8}\)
\(\frac{4}{5}\text{ x }\frac{15}{8}\text{ : }\frac{5}{7}=\frac{4}{5}\text{ x }\frac{15}{8}\text{ x }\frac{7}{5}=\frac{4\text{ x }15\text{ x }7}{5\text{ x }8\text{ x }5}=\frac{21}{10}\)
\(\frac{2}{3}+\frac{3}{4}+\frac{4}{5}=\frac{40}{60}+\frac{45}{60}+\frac{48}{60}=\frac{133}{60}\)
\(\frac{8}{5}+\frac{7}{6}+\frac{10}{9}+\frac{1}{2}=\frac{144}{90}+\frac{105}{90}+\frac{100}{90}+\frac{45}{90}=\frac{197}{45}\)
\(\frac{15}{17}-\frac{11}{13}+\frac{1}{26}=\frac{390}{442}+\frac{374}{442}+\frac{51}{442}=\frac{815}{442}\)
\(\frac{9}{12}\times\frac{4}{3}:\frac{8}{5}=1:\frac{8}{5}=\frac{5}{8}\)
\(\frac{4}{5}\times\frac{15}{8}:\frac{5}{7}=\frac{3}{2}:\frac{5}{7}=\frac{21}{10}\)
x +\(\frac{3}{2}\)X \(\frac{3}{2}\)=\(\frac{27}{4}\)
x +\(\frac{3}{2}\) = \(\frac{27}{4}\):\(\frac{3}{2}\)
x +\(\frac{3}{2}\) = \(\frac{54}{12}\)=\(\frac{18}{4}\)=\(\frac{9}{2}\)
x =\(\frac{9}{2}\)-\(\frac{3}{2}\)
x =\(\frac{7}{2}\)
CHÚC BẠN HỌC TỐT
\(x+\frac{3}{2}\times\frac{3}{2}=\frac{27}{4}\)
\(x+\frac{9}{4}=\frac{27}{4}\)
\(x=\frac{27}{4}-\frac{9}{4}\)
\(x=\frac{18}{4}\)